Contributions of Socioneuroscience to Research on Coerced and Free Sexual-Affective Desire - Racionero-Plaza, Sandra; Puigvert, Lídia; Soler-Gallart, Marta; Flecha, Ramon (Frontiers in Behavioral Neuroscience, 2022)
Neuroscience has well evidenced that the environment and, more specifically, social experience, shapes and transforms the architecture and functioning of the brain and even its genes. However, in order to understand how that happens, which types of social interactions lead to different results in brain and behavior, neurosciences require the social sciences. The social sciences have already made important contributions to neuroscience, among which the behaviorist explanations of human learning are prominent and acknowledged by the most well-known neuroscientists today. Yet neurosciences require more inputs from the social sciences to make meaning of new findings about the brain that deal with some of the most profound human questions. However, when we look at the scientific and theoretical production throughout the history of social sciences, a great fragmentation can be observed, having little interdisciplinarity and little connection between what authors in the different disciplines are contributing. This can be well seen in the field of communicative interaction. Nonetheless, this fragmentation has been overcome via the theory of communicative acts, which integrates knowledge from language and interaction theories but goes one step further in incorporating other aspects of human communication and the role of context. The theory of communicative acts is very informative to neuroscience, and a central contribution in socioneuroscience that makes possible deepening of our understanding of most pressing social problems, such as free and coerced sexual-affective desire, and achieving social and political impact toward their solution. This manuscript shows that socioneuroscience is an interdisciplinary frontier in which the dialogue between all social sciences and all natural sciences opens up an opportunity to integrate different levels of analysis in several sciences to ultimately achieve social impact regarding the most urgent human problems.